John A. Burns : the man and his times - Boylan, Dan (Latitude 20 book., 2000)
The period 1945-1975 is often referred to as "The Burns Years" in Hawai'i history books, and rightfully so. John A. Burns looms as Hawai'i's most significant political figure of the last half of the twentieth century. Burns entered politics at the close of World War II, working closely with organized labor leaders and Japanese-American war veterans to forge a Democratic party that would be an instrument of social change in Hawai'i. For twelve years, over the course of three successive terms as governor, Burns helped to shape many important elements of Hawai'i's social and political structure that continue to this day. The central feature of Burns' success was the coalition of labor and Americans of Japanese ancestry he created and worked so hard to sustain as party leader, Delegate-to-Congress, and Governor. That coalition took control of Hawai'i's legislature in 1954, its congressional delegation in 1956, and its executive office in 1962--and has held on to all three ever since